2017
DOI: 10.1007/s10120-017-0703-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of early gastric carcinoma with lymphoid stroma based on lymph node metastasis status

Abstract: Early GCLS has distinct clinicopathological features depending on age, sex, tumor location, EBV infection status, and LNM status. Tailored therapies, including endoscopic treatment, are needed based on the distinct clinicopathological features of early GCLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Regarding prevalence of LNM in intramucosal EBV‐GC, Tokunaga and Land reported none in 30 patients, and Lim et al . reported none in 32 patients.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding prevalence of LNM in intramucosal EBV‐GC, Tokunaga and Land reported none in 30 patients, and Lim et al . reported none in 32 patients.…”
Section: Discussionmentioning
confidence: 98%
“…As noted, the GCLS incidence rate has been reported to be between 1% and 4% of all GC cases, and >80% of GCLS cases are associated with EBV infection . Prevalence of MSI‐H carcinoma in GCLS has been reported to range from 7% to 39% .…”
Section: Diagnostic Accuracy and Priority Between Ebvgc And Gclsmentioning
confidence: 92%
“…Epstein‐Barr virus‐associated gastric cancer has been reported to have clinically distinct characteristics, especially in terms of a favorable prognosis, because of the host inflammatory immune response with dense lymphocyte infiltration, particularly cytotoxic T lymphocytes . Furthermore, previous studies have reported that this phenotype shows a lower frequency of LNM in the early stage .…”
Section: Clinical Relevance Of Ebvgc For Early Gcmentioning
confidence: 99%
See 2 more Smart Citations